The impact of Design Thinking on technology - López Asto, Melvin Kevin (2023)
In this article, we explore the impact of design thinking in technology, both in software development and hardware design. Technology professionals have adopted this approach when designing user interfaces, mobile applications, and websites or web platforms. By researching and empathizing with users, frictions and pain points in the user experience can be identified and user-centric solutions can be proposed that improve usability and overall satisfaction. In software development, design thinking improves the user experience by creating more intuitive applications and platforms. Results showed that the application of this approach led to significant improvements in usability, functionality and overall user satisfaction. Similarly, in hardware design, design thinking ensures that physical technology products are aesthetically appealing and functional. Products designed with this approach showed an effective combination of aesthetics and usability, resulting in greater user acceptance and a better overall experience. The synergy between design thinking and technology drives user-centered innovation, combining creativity and human focus with technological capabilities. With iteration, experimentation and complex problem-solving as key elements, design thinking and technology complement each other to create meaningful technology solutions.